2022
DOI: 10.1002/pits.22776
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the self‐regulation for science learning of middle school students with different achievement levels

Abstract: This research aims to examine the self-regulation of students with different achievement levels toward science learning based on Zimmerman's model including three phases: forethought, performance, and self-reflection. The research was conducted based on the case study from the qualitative research method. The study group consisted of 12 students who have different academic achievement levels and are studying at different levels of a middle school in Kayseri province, Turkey. The data of the research were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In line with existing research, this study found that SRL significantly impacts both flow of learning and engagement [ [15] , [32] ]. Karaca et al [ 11 ], asserted that individuals classified as self-regulated learners tend to demonstrate proactive behaviours, actively overseeing and managing their own learning processes through diverse approaches. Similarly, insufficient control over one's own learning trajectory has been associated with detrimental academic findings, including unsuccessful completion of courses and withdrawal from educational programmes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with existing research, this study found that SRL significantly impacts both flow of learning and engagement [ [15] , [32] ]. Karaca et al [ 11 ], asserted that individuals classified as self-regulated learners tend to demonstrate proactive behaviours, actively overseeing and managing their own learning processes through diverse approaches. Similarly, insufficient control over one's own learning trajectory has been associated with detrimental academic findings, including unsuccessful completion of courses and withdrawal from educational programmes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be defined as the process of planning, monitoring and assessing one's own learning to meet a particular aim [ 9 ]. Self-regulation is seen as a cyclical procedure with three distinct stages: forethought, performance and self-reflection [ 10 , 11 ]. Forethought processes take place prior to learning and include a task analysis phase, such as goal setting and tactical planning, as well as self-motivational and self-reflection phases, which are impacted by self-control and self-observations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations